A Multidisciplinary Spine Clinic Model Significantly Reduces Lead Times for Appropriate Specialist Visit and Appropriate Intervention in an Underserved Population: A Case Control Pilot Study. (1st September 2019) - Longo, Michael; Gelfand, Yaroslav J; Gitkind, Andrew I; Yassari, Reza; Yanamadala, Vijay
Abstract: INTRODUCTION: Spinal disorders are a leading cause of disability and lost productivity. Streamlining the route to specialist consultation and/or intervention can mitigate healthcare costs and improve patient outcomes and satisfaction. We instituted a multidisciplinary spine clinic (MSC) with physicians from neurosurgery, orthopaedics, pain medicine, and physiatry, where patients are simultaneously seen by providers from all these specialties, as appropriate. We hypothesized that patients from an underserved population initially seen in the MSC would experience reduced lead times to specialist visits and appropriate interventions compared to similar patients seen in a traditional unidisciplinary neurosurgery clinic (UDC). METHODS: Records from 150 consecutive outpatients seen by a spine-specialized neurosurgeon either in the MSC or UDC from April 2018 July 2018 were abstracted. Multiple linear regression was used to determine if utilization of a MSC led to shorter lead times from initial visit with a spine surgeon (IV) to pain specialist visit (SV) and/or intervention. RESULTS: The analytic sample consisted of 150 patients (n = 49 UDC, n = 101 MSC). Median time to SV and intervention in the UDC were 49 d (IQR 32–111) and 63 d (IQR 42–172), respectively. In the MSC, median time to SV was 20 d (IQR 0-38) and median time to intervention was 43 d (IQR 22–79). After controlling for differences between the two groups, multivariate analysis showed that the time to SV was reduced by 45 d (coef. −45.9, 95% CI [−69.5, −22.2], P < .001) and time to intervention was reduced by 60 d (coef. −55.0, 95% CI [−94.1, −15.8], P = .007) for patients seen in the MSC. CONCLUSION: By centralizing providers in a MSC, outpatients with degenerative spinal conditions experienced shorter lead times to specialist consultation and intervention. As the direct and indirect costs of caring for spinal diseases balloon, implementation of MSCs can improve care coordination for patients. This model can be implemented successfully for socioeconomically disadvantaged populations.